The Relationship between the Knowledge of Third Trimester Pregnant Women and the Implementation of Early Breastfeeding Initiation - Nurlaily Z, Sri; Pulukadang, Astin; Rasyid , Puspita Sukmawaty; Saleh, Ummi Kaltsum S.; Ida, Andi Syintha; Hikmandayani, Hikmandayani (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Early Initiation of Breastfeeding has an important role in the success of exclusive breastfeeding. Early Initiation of Breastfeeding is also one solution to reduce the risk of bleeding among postpartum women. An increase in knowledge and understanding of pregnant women about Early Initiation of Breastfeeding may support the successful implementation of Early Initiation of Breastfeeding. This study aims to determine the effect of knowledge of pregnant women in the third trimester on the implementation of Early Initiation of Breastfeeding. This was an analytical observational study with a cross-sectional design. The study was conducted in June-July 2019. The samples consisted of 30 respondents selected by purposive sampling based on certain inclusion criteria. Data were analyzed using the chi-square test to determine the effect of knowledge of pregnant women in the third trimester on the implementation of early initiation of breastfeeding. The results showed that the majority of respondents had good knowledge and performed early initiation of breastfeeding as many as 27 people (90%). Furthermore, 3 people (10%) had poor knowledge and did not perform early initiation of breastfeeding. It was obtained a p-value of 0.000 <0.05. Such findings revealed that knowledge of pregnant women was one of the factors that can support the successful implementation of Early Initiation of Breastfeeding. It is expected that healthcare workers and related parties can increase the provision of information about the importance of early initiation of breastfeeding, so as to increase knowledge as well as creating better implementation of early initiation of breastfeeding.